Diurnal variation of convective precipitation during the flood season in Fujian Province, China - Wang, Qianyun; Tang, Junlin; Zhang, Yuxuan; Li, Yanan (Frontiers in Earth Science, 2024)
Utilizing hourly observational data from automatic weather stations across Fujian Province from 2008 to 2020, this study defined and classified concepts and thresholds for convective precipitation, short-duration convective precipitation, long-duration convective precipitation, localized heavy precipitation, and widespread heavy precipitation. We explored the fundamental diurnal climatic characteristics of convective precipitation during the flood season in Fujian Province’s complex terrain. The results indicate the following. 1) Convective precipitation during the flood season exhibits distinct diurnal variation, with a significant spatial distribution along mountainous and coastal terrains. 2) The frequency of precipitation during the pre-flood season is higher and its intensity is lower than in the post-flood season. Due to differing primary weather systems influencing each period, resulting in substantial differences in the spatial distribution of precipitation frequency and intensity. 3) Both short-duration and localized precipitation show pronounced afternoon peaks in their diurnal patterns, predominantly occurring on windward slopes, highlighting mechanisms of afternoon moist convection and orographic lifting, whereas long-duration and widespread precipitation lack diurnal variation, reflecting the influence of large-scale circulation. These results will help forecasters better understand the unique precipitation characteristics of Fujian Province.